Statistical models for survey data from multiple countries on a parenting intervention programme - Van Zyl, Heiletjé (Department of Statistical Sciences, 2026)
Violence against children remains a significant world-wide issue, though disproportionately affecting low- and middle-income countries (LMICs) more compared to high-income countries (HICs), where the prevalence thereof is generally underestimated due to under-reporting and narrow definitions of what constitutes child abuse. To address this, the World Health Organization (WHO), alongside other agencies, aim to achieve the implementation of the INSPIRE: Seven Strategies for Ending Violence Against Children guidelines as part of the 2030 Sustainable Development Goals (SDGs). A pivotal prevention strategy part of the guidelines is evidence-based parenting intervention programmes (PIPs) like Parenting for Lifelong Health (PLH). This initiative, which involves the designing, testing, and disseminating of a suite of group-based, affordable, and adaptable parenting programmes for either young children (PLH-Kids) or adolescents (PLH-Teens) particularly in resource-constrained settings, has become crucial to the attainment of the WHO and fellow collaborators' long-term objective. However, it is of specific interest to investigate the extent to which PLH is able to extend efforts at a large-scale. Thus, this dissertation will focus upon the PLH Scale-up of Parenting Evaluation Research (SUPER) study for adolescents where the PIP has been delivered in seven different LMICs (Botswana, Democratic Republic of Congo (DRC), Eswatini, South Sudan, Tanzania, Zambia, and Zimbabwe). The efficacy of scaling-up is ascertained by employing Generalized Linear Mixed-Effects Models (GLMEMs) to analyse different outcome measures (with an emphasis on both harsh and positive parenting practices as well as attitude towards corporal punishment) self-reported by caregiver-adolescent dyads across alternative implementations of PLH-Teens, both in the usual (typical pre-post design of Zambia) and in a modified (adapted stepped-wedge cluster randomized trial (SW-CRT) design of Botswana) context. A more general impression of effectiveness is finally established by combining all seven, country-specific GLMEM results via a meta-analysis. It is found that, irrespective of country setting or implementation context, PLH-Teens PIP substantially reduces harsh parenting practices and poor supervision techniques, only slightly promotes positive parental involvement, and fosters notably less acceptable attitudes towards using corporal punishment in caregiver-adolescent dyads. Overall, this indicates that PLH can successfully be adapted and scaled-up to contribute to the global prevention of child maltreatment.